Sex difference in BAT thermogenesis depends on PGC-1α–mediated phospholipid synthesis in mice - Akira Takeuchi; Kazutaka Tsujimoto; Jun Aoki; Kenji Ikeda; Nozomu Kono; Kuniyuki Kano; Yoshihiro Niitsu; Masato Horino; Kazunari Hara; Rei Okazaki; Ryo Kaneda; Masanori Murakami; et al. (Nature Communications)
Abstract Brown adipose tissue (BAT), a thermogenic tissue that plays an important role in systemic energy expenditure, has histological and functional sex differences. BAT thermogenic activity is higher in female mice than in male mice. However, the molecular mechanism underlying this functional sex difference has not been fully elucidated. Herein, we demonstrate the role and mechanism of PGC-1α in this sex difference. Inducible adipocyte-specific PGC-1α knockout (KO) mice display mitochondrial morphological defects and decreased BAT thermogenesis only in females. Expression of carbohydrate response-element binding protein beta (Chrebpβ) and its downstream de novo lipogenesis (DNL)-related genes are both reduced only in female KO mice. BAT-specific knockdown of ChREBPβ displays decreased DNL-related gene expression and mitochondrial morphological defects followed by reduced BAT thermogenesis in female wild-type mice. Lipidomics reveals that, PGC-1α increases ether-linked phosphatidylethanolamine (PE) and cardiolipin(18:2)4 levels through Chrebpβ-dependent and -independent mechanisms in female BAT. Furthermore, PGC-1α enhances the sensitivity of female BAT estrogen signaling, thereby increasing Chrebpβ and its downstream DNL-related gene expression. These findings demonstrate that PGC-1α–mediated phospholipid synthesis plays a pivotal role in BAT thermogenesis in a sex-dependent manner.